2021
DOI: 10.1101/2021.02.08.430194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The envelope cytoplasmic tail regulates HIV-1 assembly and spread

Abstract: The HIV-1 envelope (Env) is an essential determinant of viral infectivity, tropism and spread between T cells. Lentiviral Env contain an unusually long 150 amino acid cytoplasmic tail (EnvCT) but the function of the EnvCT and conserved domains within it remain largely uncharacterised. Here we identified a highly conserved tryptophan motif at position 757 (W757) in the LLP-2 alpha helix of the EnvCT as a key determinant for HIV-1 replication and spread between T cells. Strikingly we find that mutating W757 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…In addition to this negative charge, positive charges positioned on the same face of the helix are also important. Previous studies have suggested several possible functions for the LLP-2, including maintaining Env in a prefusogenic state ( Lu et al, 2008 ; Postler and Desrosiers, 2013 ; Murphy et al, 2017 ), regulating viral assembly and egress ( Snetkov et al, 2021 ), or mediating matrix-Env interactions ( Alfadhli et al, 2019 ). The function of these charged residues in viral fusion or assembly remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this negative charge, positive charges positioned on the same face of the helix are also important. Previous studies have suggested several possible functions for the LLP-2, including maintaining Env in a prefusogenic state ( Lu et al, 2008 ; Postler and Desrosiers, 2013 ; Murphy et al, 2017 ), regulating viral assembly and egress ( Snetkov et al, 2021 ), or mediating matrix-Env interactions ( Alfadhli et al, 2019 ). The function of these charged residues in viral fusion or assembly remains to be determined.…”
Section: Discussionmentioning
confidence: 99%